Personality and Motives for Self-Employment - Abu H. Ayob; Hazrul Izuan Shahiri; Hamizah Abd Hamid; Wan Kamal Mujani (European Journal of Psychology Open)
Abstract: Introduction: Personality is one of the dominant intrinsic determinants in understanding human behavior, including the economic actors. Although considerable research has examined the typical characteristics of entrepreneurs, scholars have mostly neglected the binary motives for self-employment. This research examines the relationship between the Big Five personality traits and opportunity-versus-necessity entrepreneurship. In particular, we study how Openness to Experience, Conscientiousness, Extroversion, Agreeableness, and Neuroticism are related to the propensity for being opportunity (creative) entrepreneurs as opposed to necessity (routine) entrepreneurs. Methods: This study employed probit regression to examine the relationship between the Big Five personality traits and opportunity versus necessity entrepreneurship. Specifically, we test the hypotheses using World Values Survey Wave 6 data among 3,859 individuals in 20 countries. Results: After controlling for other demographic and institutional factors, we found that opportunity entrepreneurs are more open but less conscientious and less agreeable than necessity entrepreneurs. Conclusion: From this, we learn that entrepreneurs’ personalities are heterogeneous based on their motive for self-employment.